Spark Plasma Sintering and Upsetting of a Gas-Atomized/Air-Atomized Al Alloy Powder Mixture - TÜNÇAY, MEHMET MASUM (SPRINGER, 2017)
Al-Zn-Mg-Cu alloy powder, Alumix 431D, was modified by replacing the native air-atomized pure Al particles with gas-atomized pure Al. Samples were sintered using spark plasma sintering (SPS), and upset forging was applied to the sintered samples by SPS. Densities over 98 and 99% of theoretical were obtained for the sintered and forged samples, respectively. Microstructural analysis and characterization of all samples were done using energy-dispersive spectroscopy and x-ray diffraction. Mechanical properties were evaluated using microhardness and flexural strength and strain measurements. The microhardness value of the T6 tempered sample was comparable to that of its wrought counterpart AA7075. Particle bonding after sintering was incomplete and reveals that composite oxide layer of Al-Zn-Mg-Cu alloy powder is difficult to disrupt, and it is necessary to apply a secondary process like forging to improve particle bonding. The loss in ductility following T6 tempering is ascribed to void formation due to the dissolution of the secondary phases, remaining undissolved precipitates, and a localized lack of cohesion between particles.
Keywords: Al alloys; forging; mechanical properties; powder blend; spark plasma sintering; MG-CU ALLOY; 7075 ALUMINUM-ALLOY; MECHANICAL-PROPERTIES; SURFACE OXIDE; MICROSTRUCTURAL EVOLUTION; HEAT-TREATMENT; PRECIPITATION; CONSOLIDATION; BLEND